2002
DOI: 10.1143/jjap.41.l307
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method of Estimating Dielectric Constant for Low-k Materials

Abstract: Helium-like spectra produced by photon emission of ions with intermediate Z represent an important diagnostic for fusion plasmas and solar flares. In this work, the influence of the radiative transitions among doubly excited levels on the intensity of the associated dielectronic satellites (1s 2 nl-1s2lnl ) is analysed. Special attention is paid to the comparison between inner-shell excited satellites of n = 2 and different theoretical calculations. We described the group of n = 3 and n = 4 dielectronic satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Endo et al 27 30 and XPS analysis revealed only a small amount of oxygen in our films. The slight decrease with the frequency observed at higher frequencies is believed to result from incomplete dielectric relaxation occurring at frequencies higher than 10 kHz.…”
Section: A Dielectric Constantmentioning
confidence: 46%
“…Endo et al 27 30 and XPS analysis revealed only a small amount of oxygen in our films. The slight decrease with the frequency observed at higher frequencies is believed to result from incomplete dielectric relaxation occurring at frequencies higher than 10 kHz.…”
Section: A Dielectric Constantmentioning
confidence: 46%
“…6͑b͔͒ is relatively unchanged for all three porosities studied. According to Fukuda et al 39 the Si-H bond, with a representative refractive value of 3.201, is much more polar than the Si-O bond, which has a representative refractive value of 1.75. Also of note is that all three porosities collapse onto the same line indicating modified layer growth rate is independent of porosity.…”
Section: Reactive Species Concentrationmentioning
confidence: 99%
“…A lot of low-k materials such as organic-based low-k materials and silica-based materials have been widely investigated. Among them is an organic-based material with , which contains aromatic rings in their skeleton structure [2], [3].…”
Section: Introductionmentioning
confidence: 99%